To be where you are [compact disc, unabridged] - Karon, Jan, 1937- (A Mitford novel, 2017)
Father Tim Kavanagh struggles to find meaning in retirement, while newlyweds Dooley and Lace face a crisis that drains their bank account, and four-year-old Jack Tyler looks forward to the biggest day of his young life.